Penyusunan Strategi Bisnis Dan Strategi Operasi Usaha Kecil Dan Menengah Pada Perusahaan Konveksi Scissors Di Surabaya - Mochamad Ammar Faruq; Indrianawati Usman (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
The development of globalization era gives us tighter business competition in many sector including UKM (Usaha Kecil dan Menengah). A company tends to make a good business and strategic operation to gives a positive effect for all UKM doers to face business competition. This case is very interesting to be researched and taught how business and operation strategic arrangement provide high competitiveness factor towards the company. This research included as descriptive-explorative qualitative research. This research did not need any theory or hypotheses but only use some prepared questions as a guide to get primary data about information which is the first data that required for this research (Moleong: 1998). This research object is one of the UKM convection called Scissors Convection on jl. Simorejo 6, Surabaya. Data analysis technique in this research are using content analysis and matrixes as the instrument. Matrixes that used in this data analysis are External Factor Evaluation (EFE), Internal Factor Evaluation (IFE), Competitive Profile Matrix (CPM), Strengths-Weaknesses-Opportunities-Threats (SWOT), Grand Strategy, and Quantitative Strategic Planning Matrix (QSPM). Also, triangulation technique as source consistency experiment towards data and operation strategy based on Roger G. Schroeder’s Operation Management. Result of this research proved that the appropriate business strategy for Scissors Convection are product development strategy for variation and product design while the best operation strategy is product innovator strategy.